Arab Republic of Egypt : Ex-Post Evaluation of Exceptional Access Under the 2020 Stand-By Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Arab Republic of Egypt. (IMF Staff Country Reports; Country Report, 2022)
The Executive Board approved a 12-month Stand-By Arrangement (SBA) on June 26, 2020, to support the Egyptian authorities' response to the COVID-19 pandemic. The SBA, at 184.8 percent of quota, was part of a two-step support strategy that was preceded by a purchase under the Rapid Financing Instrument on May 11, 2020, at 100 percent of quota. Both reviews of the SBA were concluded on time and all program conditionality was met. The arrangement expired on June 25, 2021.